CuCl/TBHP catalyzed synthesis of amides from aldehydes and amines in water. Issue 6 (10th February 2016) - Lu, Shao-Yi; Badsara, Satpal Singh; Wu, Yi-Chun; Reddy, Daggula Mallikarjuna; Lee, Chin-Fa
Graphical abstract: A CuCl/TBHP catalyzed amidation of aldehydes with amines under aqueous media is described. Both aliphatic and aromatic aldehydes coupled with a variety of amines under the reaction conditions employed. Abstract: A CuCl/TBHP catalyzed amidation of aldehydes with amine under aqueous media is described. Both aliphatic and aromatic aldehydes coupled with a variety of amines under the reaction conditions employed.